A Review on Optimal Siting and Sizing of DSTATCOM - Dansarki Nanly Wesley; Abubakar Abdulkarim; P.U. Okorie; Adamu Halilu Jabire; Sani Saminu; Nasir Faruk; I.S. Madugu; A. U. Lawan; Iswadi Hasyim Rosma (Journal of Applied Materials and Technology, 2021)
The continuous demand for electrical energy by industries and domestic users have stressed the electricity consumption to a high level. Because most components of domestic and industrial systems are made of power electronics devices in their designs. In addition, modern electrical power distribution networks (DNs) are subjected to major disturbances. Consequently, today’s power system is laden with power quality problems such as excessive energy losses, voltage deviations, poor power factor (PF), voltage instability and reliability issues to mentioned just a few. To forestall these disturbances, Distribution Engineers have introduced the use of Custom Power Devices (CPDs) in order to reduce power losses so as improve power quality. Amongst CPDs, Distribution Static Compensator (D-STATCOM) proves most promising in minimizing power quality issues because it generates minimal harmonics, waste less power, has small size, high regulatory capability and cost effective. Researchers in recent years have focused on methodologies required for identifying the most suitable location and rating of D- STATCOM device based on divergent views. However, to date, only one author has so far reviewed a paper on this aspect of study. This paper discusses the latest study on appropriate installation and rating of D-STATCOM techniques for balanced and unbalanced radial distribution networks (UBRDNs). The paper has also provided a comprehensive literature study on the location of DSTATCOM in RDNs for power loss reduction and power quality enhancement. Comparative analyses of various techniques for development of DSTATCOM Objective functions and constraints; Merits and Demerits are presented.